Description and quantitative analysis of the dentition of the southern thorny skate Amblyraja doellojuradoi in the Southwest Atlantic - Delpiani, Gabriela Elina (2017)
A description of the tooth morphology of 234 jaws from the southern thorny skate Amblyraja doellojuradoi in the south-west Atlantic Ocean is given. Seven rows of teeth were selected and length and width of each tooth in these rows were measured. It was found that functional series corresponds to the third teeth and the average width and length of these teeth were compared among jaws, maturity stages, sexes and rows. Generalized linear models were used to determine the subset of measures that most contribute to explain the variability between groups. It was observed that males have longer teeth than females, but the teeth of females are wider. These differences are attributed to reproductive behaviour, in which males bite females to hold them during copulation. This study provides a description of the teeth of A. doellojuradoi, supplying a valuable tool for identification of species. In addition, the establishment of the main variations observed in the dentition, improves the understanding of the species' biology.